Study of Factors Associated with Sarcopenia in COPD Patients (Medicine Today, 2021)
Introduction: Sarcopenia is frequently associated with chronic diseases such as chronic obstructive pulmonary disease (COPD). Sarcopenia can be classified as physical frailty where frailty is associated with adverse health outcomes. Sarcopenia was found to be associated with worsening lung function in male COPD patient. Objective was to find out the factors associated with sarcopenia in COPD patients.Materials & Methods: This was cross-sectional observational study was carried out Different Privet Medical in Chandpur and Chandpur Medical College Hospital, Chandpur. Patients diagnosed with COPD according to Global Initiative for Chronic Obstructive Pulmonary Disease (GOLD) guidelines were included in this study. Exclusion criteria were unstable cardiac disease, an exacerbation within the preceding 4 weeks, predominant neurological limitation to walking (eg, significant hemiplegia) or contraindication to bioelectrical impedance analysis (BIA) including an implanted pacemaker or defibrillator. All participants gave written informed consent. EWGSOP criteria were applied to outpatients with stable COPD.Results: In uniavariate analysis, age, moderate COPD, severe COPD, obesity, non-elective admission over the past 12 months, MMRC scale and MAP were significantly associated with sarcopenia. In multivariate analysis, age, moderate COPD, severe COPD, obesity and MMRC scale were significantly associated with sarcopenia.Conclusion: Prevalence of sarcopenia was 26%. Independent factors associated with sarcopenia Age (>70 years) years (adjusted odds ratio (AOR) 4.387. Sarcopenia affects about one-quarter of COPD patients. Age, severity of COPD, MMRC scale, and BMI status were the factors associated with sarcopenia.Medicine Today 2021 Vol.33(1): 50-53